Self-Identification and Self-Hate in The Bluest Eye, Sula and Tar Baby by Toni Morrison - Tomaštíková, Eva (2006)
The thesis focuses on the theme of a black woman's self-identification which is analysed in Toni Morrison's The Bluest Eye, Sula and Tar Baby. This study is approached from the point of view of history and sociology. The theoretical part deals with the black inferiority as a result of history and with the problem of a black woman's identity resulting from her attempt at assimilation into American society. As for the analytical chapters, they try to prove through the female characters that it is not the best way for a black woman to desire identification with a white woman because there exist a lot of racial barriers that are not easily broken down.